Diseño del centro administrativo municipal de Villavicencio a través de la arquitectura sostenible e inmótica (2020)
The main objective of this research is to design the Municipal Administrative Center, of the City of Villavicencio, to improve physical, spatial and social conditions, through the implementation of sustainable and Inmotic architecture.